Education For Young Generations in The Church - Wennar, Wennar; Mukti, Guntur Hari (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The younger generation is the future successor of leadership in God’s church. For this reason, it is necessary to prepare by conducting education from an early age. The research method used is qualitative research with theological studies by utilizing the Bible and literature according to the subject matter, then analyzed and presented descriptively. Thus, a true and strong foundation will be laid for the spiritual growth of the younger generation, so that they become like Christ to do God’s will in their time. The education of the younger generation includes the example of leaders, teaching God’s Word, fellowship with brothers and sisters and also involvement in ministry in the church and community. So that the church can be a witness for Christ throughout the ages.